Boosting Potassium Storage by Integration Advantageous of Defect Engineering and Spatial Confinement: A Case Study of Sb2Se3. Issue 49 (17th November 2020) - Sheng, Binbin; Wang, Lifeng; Huang, Huijuan; Yang, Hai; Xu, Rui; Wu, Xiaojun; Yu, Yan
Abstract: The potassium ion batteries (KIBs) based on conversion/alloying reaction mechanisms show high theoretical capacity. However, their applications are hampered by the poor cyclability resulting from the inherent large volume variations and the sluggish kinetics during K + repeated insertion/extraction process. Herein, taken Sb2 Se3 as a model material, by rational design, nickel doped‐carbon coated Sb2 Se3 nanorods (denoted as (Sb0.99 Ni0.01 )2 Se3 @C) are prepared through combined strategies of the conductive encapsulation and crystal structure modification. The carbon coating acts as an efficient buffer layer that maintains superior structural stability upon cycling. The introduction of Ni atoms can enhance electrical conductivity, leading to outstanding rate performance, which are confirmed by density functional theory calculation. The (Sb0.99 Ni0.01 )2 Se3 @C displays excellent reversible capacity (410 mAh g −1 at 0.1 A g −1 after 100 cycles) and unprecedented rate capability (140 mAh g −1 at 10 A g −1 ). Furthermore, KFeHCF//(Sb0.99 Ni0.01 )2 Se3 @C full cell exhibits a high specific capacity (408 mAh g −1 at 0.1 A g −1 ), superior rate capability (260 mAh g −1 at 2 A g −1 ). This work can open up a new avenue for the design of stable conversion/alloying‐based anodes for high energy density KIBs. Abstract : Nickel doped‐carbon coated Sb2 Se3 nanorods ((Sb0.99 Ni0.01 )2 Se3 @C) are designed as anode for K‐ion battery. The (Sb0.99 Ni0.01 )2 Se3 @C demonstrates a remarkable reversible capacity of 410 mAh g −1 at 0.1 A g −1 after 100 cycles, which results from the advantages of defect engineering and spatial confinement.